Social exclusion and the criminal justice system: a comparative analysis - García España, Elisa; Cerezo Domínguez, Ana Isabel (New advances in crime and social harm, 2024)
A roadmap for comparative criminal policy research / José Becerra-Muñoz -- Social inclusion and comparative criminal justice policy / José Luis Díez-Ripollés -- RIMES : an instrument to compare national criminal justice policies from the social exclusion dimension / José Luis Díez-Ripollés -- Constructing, validation, and application of the RIMES instrument : methodological issues / Lorea Arenas-García -- The pilot application of RIMES instrument in Spain / Elisa García-España -- Pool 1. Control of public spaces / Pablo Rando-Casermeiro -- Pool 2. Legal safeguards / Bertha Verónica Prado-Manrique -- Pool 3. Sentencing and sanction systems / María Izco-Rincón -- Pool 4. Harshest penalties / Noelia Corral-Maraver -- Pool 5. Prison rules / Lorea Arenas-García -- Pool 6. Preventive intervention / Elena Casado-Patricio & Cristina Güerri -- Pool 7. Legal and social status of offenders and ex-offenders / María Contreras-Román -- Pool 8. Police and criminal records / Juan Antonio Aguilar-Jurado -- Pool 9. Youth criminal justice / Fátima Pérez-Jiménez -- Overview of the RIMES application : insights for comparative criminal policy / Elisa García-España & Anabel Cerezo.